2019
DOI: 10.2147/clep.s200748
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identifying cerebral palsy from routinely-collected data in England and Wales</p>

Abstract: Purpose: An observational study using routinely-collected health care data to describe the extent to which children and young people (CYP) with cerebral palsy (CP) can be identified and the prevalence of CP can be estimated. Patients and methods: Routinely-collected anonymized data, for CYP (aged 0–25 years old between 1 January 2004 and 31 December 2014) were analyzed in two linked datasets, from England and Wales respectively. Datasets included National Health Service; Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…While the NICPR relies on information provided by practitioners and hence may underestimate cases, it nevertheless provides the best opportunity to study a cohort of confirmed cases of CP. Use of UK routinely collected healthcare data alone to identify children and young adults with CP has been shown to be severely limited by quality of coding 13 . However, use of the NICPR has allowed exploration of service use in a well‐defined population of children and young adults with CP, compared with those without.…”
Section: Discussionmentioning
confidence: 99%
“…While the NICPR relies on information provided by practitioners and hence may underestimate cases, it nevertheless provides the best opportunity to study a cohort of confirmed cases of CP. Use of UK routinely collected healthcare data alone to identify children and young adults with CP has been shown to be severely limited by quality of coding 13 . However, use of the NICPR has allowed exploration of service use in a well‐defined population of children and young adults with CP, compared with those without.…”
Section: Discussionmentioning
confidence: 99%
“…The administrative in-patient data lacks detailed information about disease severity and medical treatments; comorbidities are dependent upon reliable ICD-10 coding, and variation in documentation and coding of diagnoses could contribute to measurement error 34 . However, in Wales, routinely collected population-scale EHR data are sufficiently robust and accurate to be used in research or for health services planning 35 . We could not analyse the direct impact of possible differences in treatment intensity during ICU admission, as comparative data are not available currently in the SAIL Databank in the hospital cohort.…”
Section: Limitationsmentioning
confidence: 99%
“…The administrative in-patient data lacks detailed information about disease severity and medical treatments; comorbidities are dependent upon reliable ICD-10 coding, and variation in documentation and coding of diagnoses could contribute to measurement error 34 . However, in Wales, routinely collected population-scale EHR data are su ciently robust and accurate to be used in research or for health services planning 35 . We could not analyse the direct impact of possible differences in treatment intensity during ICU admission, as comparative data are not available currently in the SAIL Databank in the hospital cohort.…”
Section: Limitationsmentioning
confidence: 99%